Hurdles in the Pipeline. - Kekelis, Linda S.; Ancheta, Rebecca Wepsic; Heber, Etta (Frontiers: A Journal of Women Studies, 2005)
The article deliberates on a program entitled "Techbridge," to assess the prospect of a career for girls in technology. The primary sources of data for the study are in-depth interviews and focus groups with 126 Techbridge girls and 34 of their parents or guardians. The girls ranged in age from eleven to nineteen years old, with most in the twelve- to fifteen-year-old range. The researchers selected girls who had a broad range of involvement and skill levels within their programs and who reflected the range of racial and socioeconomic backgrounds in their schools. The goals of Techbridge were to engage girls in learning and using technology, to embolden their plans for further study in technology, and to increase their interest in pursuing careers in technology. Girls told them that even though they enjoyed working on computers in Techbridge, they would not want jobs where they look at a computer screen all day and come home with headaches. Not all girls in Techbridge were reluctant to consider a career in a technical or scientific area. Some discussed their plans to become a Web designer, graphic artist, or computer technician.